Impact of transurethral resection of bladder tumors on sexual function and quality of life using ePROMs in patients with bladder cancer: a prospective cohort study - Menold, Hanna; Grüne, Britta; Koenig, Julian; Lenhart, Maximilian; Waldbillig, Frank; Kowalewski, Karl-Friedrich; Michel, Maurice Stephan; Kriegmair, Maximilian; Neuberger, Manuel; Wessels, Frederik (World journal of urology, 2025)
Introduction The impact of transurethral resection of bladder tumors (TURBT) on patients’ quality of life (QoL) and sexual function is underrepresented in the literature. Therefore, this study aimed to evaluate sexual function and QoL following TURBT, using electronic patient reported outcome questionnaires (ePROMs). Methods Patients undergoing TURBT were surveyed using a digital ePROM system (Heartbeat Medical). Sexual function and QoL were assessed using the Male/Female LUTS Sexual Function module (ICIQ-MLUTSsex/FLUTSsex) at 3, 6 and 12 months postoperatively and the EORTC QLQ-NMIBC 24. Linear mixed-effects models were used to identify influencing factors, adjusting for baseline. Repeated measures ANOVA tested differences in domain scores over time. Results 197 patients completed the survey, of whom 77% (n = 151) were men. Based on the ICIQ-MLUTSsex sexual function was significantly impaired at 3, 6 and 12-months postoperatively compared to baseline (p = 0.005; p = 0.004; p = 0.017). Age was the strongest factor for reduced male sexual function (ICIQ-MLUTSsex and QLQ-NMIBC24: p < 0.001). Subdomain analysis revealed negative effects on ejaculation (p = 0.044) and urinary symptoms (p = 0.031) up to 6 months. No differences were observed for the female population. Conclusion TURBT may result in long-term impairment of sexual function in male patients, whereas no such effect was observed in female patients within this cohort.
Online veröffentlicht: 10. Juni 2025
Gesehen am 02.10.2025